Monitoring consumptive resource use in South African national parks - Wessel Vermeulen; Nicola van Wilgen; Kyle Smith; Mbulelo Dopolo; Louise Swemmer; Wendy Annecke; Hugo Bezuidenhout; Graham Durrheim; Nick Hanekom; Howard Hendricks; Melodie McGeoch; Ntombizodwa Ngubeni; et al. (Koedoe: African Protected Area Conservation and Science, 2019)
Monitoring is an essential component of measuring the performance of protected areas. This requirement led to the development of a biodiversity monitoring system for South African National Parks (SANParks). The system comprises of ten major programmes, each focusing on a core area of conservation biodiversity monitoring, with resource use being one of the focal areas. With the growing appreciation of the importance of natural resources for the socio-economic well-being of communities and other stakeholders, sustainable resource use is an important component of the management of natural areas and national parks. To gauge sustainability, a sound monitoring and research programme that fits within the context of the SANParks’ adaptive management approach towards social-ecological system management is required. The purpose of this article was to define the context and scope in which consumptive resource use takes place within SANParks and to outline the criteria necessary for developing a sound monitoring programme to assess the sustainability of such use. The monitoring programme is structured in view of the fact that sustainable resource use is achievable only where all dimensions of sustainability (social, economic and ecological) are considered simultaneously. In terms of the social and economic dimensions of sustainability, the programme provides for assessing stakeholder needs, trends in resource use and the social and economic impacts of resource use. Monitoring that relates to the ecological dimension of sustainability of biological resource use deals with the rate of turnover and population dynamics of target species, as well as harvest impact. In terms of abiotic (non-renewable) resources, monitoring deals with sound management practices to minimise impact on the environment, and to optimise benefits through responsible use.